Louise Stein, The Iberian Peninsula and its New World Colonies: The Spanish and Portuguese heritage - Nelson, Bernadette (Revista Portuguesa de Musicologia, 2014)
Recensão: Louise Stein, The Iberian Peninsula and its New World Colonies: The Spanish and Portuguese heritage